POTENSI MEMBRAN MIKROFILTRASI DAN ULTRAFILTRASI UNTUK PENGOLAHAN LIMBAH CAIR BERMINYAK - Maria Widyasmara; Cindika Kusuma Dewi; Nita Aryanti (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
Oily wastewater in the form of stable oil in water emulsion is found as one source of industrialwastewater in Indonesia. Conventional wastewater treatment has several limitations and is not able to achieverequirement for effluent standard. Nowadays, membrane microfiltration and ultrafiltration have been used forwater purification as well as wastewater treatment. Studies on the application of microfiltration andultrafiltration for wastewater have been conducted. However, the studies used real wastewater consistingcomplex compound. In this research a model of oily wastewater was used. The model of oily wastewatercomprised an oil in water emulsion stabilized with a surfactant. By using this model, it is expected that analysisof membrane performance based on permeate flux and rejection can be conducted more comprehensively. Thisresearch used microfiltration and ultrafiltration membrane and the oily wastewater model was made by mixingTween 80 with concentration of 2% with several types oil (vegetable oil, diesel oil dan cutting oil). The researchis carried out in order to obtain wastewater and membrane characteristic as well as the influence of TMP, oilytypes and oil concentration on membrane performance based on permeate flux, COD and surfactantrejection.Based on this research characteristics of oily wastewater could be obtained. In general, increase ofTMP resulted on higher permeate flux. By varying the oily type, it was found that the vegetable oil has thehighest permeate flux, the effect of oil concentration on permeate flux in addition was depend on TMP. When theTMP was 1 bar, the increase of oil concentration produced lower flux. However at TMP of 2 bar, the permeateflux is independent on oil concentration. Experimental works using ultrafiltration resulted on 94,89 – 98,83%rejection of COD and 69 – 86% rejection of surfactant. Based on this research it is concluded that theultrafiltration is capable to treat oily wastewater in the form of stable oil in water emulsion.